2023
DOI: 10.3390/w15091733
|View full text |Cite
|
Sign up to set email alerts
|

Review on Drip Irrigation: Impact on Crop Yield, Quality, and Water Productivity in China

Abstract: The scarcity of freshwater resources is a global concern that is exacerbated by an increasing global population and climate change induced by global warming. To address this issue, the largest water-consuming sector has taken a series of measures termed as drip irrigation schemes. The primary purposes of drip irrigation are to reduce water scarcity near the root zone, reduce evaporation, and decrease water use. The application scope of drip irrigation is getting wider and wider, with the number of papers relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Therefore, salt leaching in drip irrigation is not significant. However, drip irrigation, through precise control of water volume and flow, significantly reduces surface evaporation and underground leakage of water (Shu et al, 2022;Yang et al, 2023), thus improving water use efficiency. could be observed that the kurtosis of the soil moisture content curves at each layer during drip irrigation was smaller than that during surface irrigation (Figure 7b and c).…”
Section: Water-salt Transport Patterns and Influencing Factorsmentioning
confidence: 99%
“…Therefore, salt leaching in drip irrigation is not significant. However, drip irrigation, through precise control of water volume and flow, significantly reduces surface evaporation and underground leakage of water (Shu et al, 2022;Yang et al, 2023), thus improving water use efficiency. could be observed that the kurtosis of the soil moisture content curves at each layer during drip irrigation was smaller than that during surface irrigation (Figure 7b and c).…”
Section: Water-salt Transport Patterns and Influencing Factorsmentioning
confidence: 99%
“…As the agricultural sector expanded, so did the use of synthetic fertilizers and pesticides. An important breakthrough in this decade was the advent of drip irrigation, which promised efficient water management and marked a move toward precision agriculture ( Xi et al., 2022 ; Yang et al., 2023 ).…”
Section: Historical Overviewmentioning
confidence: 99%
“…This approach maximizes access to oxygen, promotes growth, and reduces disease risk ( Singh, 2023 ). Simultaneously, the drip system, utilizing intricate tubing and drip emitters, allows for the precise delivery of nutrients ideal for larger or specific plant species ( Yang et al., 2023 ). Alternate growing media, such as coco coir and a blend of peat and perlite, although still considered hydroponic, have gained traction because of their impressive moisture retention and aeration capacities ( Mariotti et al., 2020 ).…”
Section: Soil and Growing Media Innovationsmentioning
confidence: 99%
“…Tujuan utama irigasi tetes adalah untuk mengurangi kekurangan air di dekat zona perakaran, mengurangi penguapan, dan mengurangi penggunaan air. Irigasi tetes dapat mengatasi kekurangan air, hemat air dan menjamin hasil panen dibandingkan dengan sistem genangan, irigasi sprinkler, dan irigasi sprinkler mikro (Yang et al, 2023).…”
Section: Gambar 1 Tanaman Vanili Umur 12 Bulanunclassified